Painted woodcut of Redpolls (birds) on the south exterior wall of the Yellowknife Inn ... - Campbell, Sandy (University of Alberta Library, 2015)
This painted woodcut installed on the south wall of the Yellowknife Inn in Yellowknife, NWT is one of a series of bird images. This image shows two common redpolls perched in a bush. This artwork is attached to the corrugated steel wall which faces south into the parking lot of the hotel and mall. ...